Finding and utilizing opinion leaders: Social networks and the power of relationships - R. Van Der Merwe; G. Van Heerden (South African Journal of Business Management, 2009)
Research suggests that consumer choice is sub-optimal: simply we satisfice. Limited data, time and expertise render our rationality `bounded'. The opinion leader offers a solution to this problem: when faced with a complex choice, we often seek the opinion of an expert. The Web has fueled an unprecedented expansion of this strategy by enabling `virtual' opinion leaders (see Web sites such as Epinions.com and Amazon.com). However, despite its rise in popularity, opinion leadership has received limited attention in the advertising literature.It is this hiatus that we address and in doing so seek to make two potentially important contributions to the wider research on opinion leadership. First, we link opinion leadership to social network theory and show that, those at individuals who are central to social networks serve as opinion leaders. Second, we challenge the assumption that opinion leadership is monomorphic (topic specific) by showing that domain-specific opinion leadership is strongly related to general opinion leadership.Our paper is set out as follows. First, we provide overviews of the literatures on opinion leadership and social networks. Second, we outline our methodology and present the results of an empirical study. Finally, we delimit the research, present a framework for identifying opinion leaders, identify key implications, and explore potential avenues for future research.
Keywords: 650